(3QMeI GdCeI aj GNJdGa GdCFeIs - (3TeS GdOjf CHh YHO Gddg eMeO Hf YHO GdQMef GdOeTbj GdTGaYj GdYKeGfjs ((3MSjf Hf MSf Hf ESeGYjd GdjeGfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CLRd EMSGfg , hCfRd bQBfg CeG HYO , aEf eYQaI GdELeGY hENJdGa GdYdeGA ef CJe GdCTjGA hPdc CeQ dGRe ai Mb GdeLJgO s
(3BNQgG (B:s
(3hbGd eGdc dGjLhR dg Pdc , aGage hGZJfe Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdYfhGfGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GNJdGa GdabgGAs